Case of HER2-Enriched Multifocal Breast Cancer Associated with Pregnancy - Khanal, Suman; Singh, Yogendra P; Shrivastav, Shreya (Journal of Institute of Medicine Nepal, 2019)
Pregnancy-associated breast cancer is less common and often presents in advanced stage. Management is similar to non-pregnant cases with trimester-specific considerations. In this case report, we present a case of worrisome mother with locally advanced multifocal pregnancy-associated breast cancer who was so much concerned about effects of neoadjuvant chemotherapy on fetus leading to its delayed initiation, and show why targeted therapy is still not within reach in a developing economy like Nepal. Short term data of chemotherapy though reveal relative safety, long term data are lacking. This may be a hindrance in counselling, when patients are more anxious and worrisome.